2000
DOI: 10.2165/00002512-200017060-00005
|View full text |Cite
|
Sign up to set email alerts
|

Topical Dorzolamide 2%/Timolol 0.5%

Abstract: Dorzolamide/timolol is a well tolerated and effective fixed combination for lowering IOP in the treatment of open-angle glaucoma and is likely to be useful in those patients who do not respond adequately to first-line monotherapy. Compared with concomitant therapy with the same 2 drugs the primary advantage is convenience, which may lead to improved compliance. Studies of compliance and comparisons with other currently available combination therapies would be useful to fully define the value of the formulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Timolol, a b-adrenergic antagonist and dorzolamide, a carbonic anhydrase inhibitor decrease IOP by inhibiting the production of aqueous humor, but through different mechanisms [25]. Previous studies have confirmed a better efficacy in lowering IOP by combination therapy than monotherapy [26][27][28] and fixed combination showed comparable clinical effect as concomitant therapy [29][30][31][32]. To our knowledge this is the first study proving the efficacy of simultaneous release of glaucoma drugs from contact lenses.…”
Section: Introductionmentioning
confidence: 99%
“…Timolol, a b-adrenergic antagonist and dorzolamide, a carbonic anhydrase inhibitor decrease IOP by inhibiting the production of aqueous humor, but through different mechanisms [25]. Previous studies have confirmed a better efficacy in lowering IOP by combination therapy than monotherapy [26][27][28] and fixed combination showed comparable clinical effect as concomitant therapy [29][30][31][32]. To our knowledge this is the first study proving the efficacy of simultaneous release of glaucoma drugs from contact lenses.…”
Section: Introductionmentioning
confidence: 99%
“…Since their action mechanism is different, they have an additive effect when administered together. [19]…”
Section: Introductionmentioning
confidence: 99%
“…It has a purite preservative (purite is a stabilized oxychloro complex acting as an oxidative preservative that is converted into natural tear components when exposed to light) that breaks down into natural tear components and may be better tolerated in people who have allergic reactions to preservatives in other eye drops. [121319]…”
Section: Introductionmentioning
confidence: 99%